2022
DOI: 10.1111/hae.14550
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of long‐term von Willebrand factor prophylaxis use in von Willebrand disease: A systematic literature review

Abstract: Background Von Willebrand Disease (VWD) is a common inherited bleeding disorder. Patients with VWD suffering from severe bleeding may benefit from the use of secondary long‐term prophylaxis. Aim Systematically summarize the evidence on the clinical outcomes of secondary long‐term prophylaxis in patients with VWD and severe recurrent bleedings. Methods We searched Medline and EMBASE through October 2019 for relevant randomized clinical trials (RCTs) and comparative observational studies (OS) assessing the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…However, this analysis adds to the limited data on the use of long-term VWF prophylaxis, specifically in this rare subtype of VWD. 22,23 The analyses of all BEs (untreated and treated; spontaneous and traumatic) and sensitivity analyses (treated and untreated spontaneous BEs; treated spontaneous and traumatic BEs) confirm efficacy results reported previously for treated spontaneous BEs in patients with severe VWD and reported herein for patients with type 3 VWD. 18 Furthermore, analyses of treated spontaneous/traumatic or all spontaneous/traumatic joint bleeds highlighted the small number of joint BEs in the study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, this analysis adds to the limited data on the use of long-term VWF prophylaxis, specifically in this rare subtype of VWD. 22,23 The analyses of all BEs (untreated and treated; spontaneous and traumatic) and sensitivity analyses (treated and untreated spontaneous BEs; treated spontaneous and traumatic BEs) confirm efficacy results reported previously for treated spontaneous BEs in patients with severe VWD and reported herein for patients with type 3 VWD. 18 Furthermore, analyses of treated spontaneous/traumatic or all spontaneous/traumatic joint bleeds highlighted the small number of joint BEs in the study.…”
Section: Discussionsupporting
confidence: 85%
“…This was not unexpected because 18/23 patients in the study had type 3 VWD, and all on‐study treated BEs were reported in patients with type 3 VWD. However, this analysis adds to the limited data on the use of long‐term VWF prophylaxis, specifically in this rare subtype of VWD 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…Minor bleeding [41] Major bleeding [41] Plasma-derived products 30-60 units/kg 40-60 units/kg 20-40 units/kg every 8-24 hours may be required Single-dose for minor bleeding and for up to 14 days after significant bleeding or surgery [42] Recombinant von Willebrand factor (rVWF) 40-50 IU/kg [43] 60-80 IU/kg [43] Subsequent doses of rVWF can be given at 40-60 units/kg every 8 to 24 hours An infusion rate of 2-15 units/kg/hour can be used [45]. Continuous infusion is also used in patients with acquired VWD and patients with alloantibodies against infused VWF Continuous infusion of VWF concentrates can reduce the clearance of infused products and decrease the total therapeutic dose and cost by as much as 50% [44] Factor VIII 50 units/kg Should be used with the initial rVWF dose to raise factor VIII by 100 IU/dL [43] VWD: Von Willebrand disease.…”
Section: Vwf Concentratesmentioning
confidence: 99%
“…Continuous infusion of VWF concentrates at a rate of 2-15 units/kg/hour can reduce the clearance of infused products, lower the total therapeutic dose and reduce cost by as much as 50% [44,45]. Continuous infusion is also used in patients with acquired VWD and alloantibodies against infused VWF.…”
Section: Vwf Concentratesmentioning
confidence: 99%
“…[7][8][9][10] In the 2021 international guidelines on the management of VWD, long-term prophylactic VWF replacement was recommended in patients with a history of severe and frequent bleeds. 5,[11][12][13] However, this recommendation was conditional based on the low certainty in evidence of effects. 5 In particular, there is limited real-world evidence demonstrating the health benefits of long-term prophylaxis in patients with VWD.…”
Section: Introductionmentioning
confidence: 99%